The Routledge international handbook of life-course criminology - Blokland, Arie Aart Jan; Geest, Victor René van der (Routledge international handbooks, 2017)
pt. I. Theory -- pt. II. Criminal careers -- pt. III. Onset and continuation -- pt. IV. Offending over the life-course -- pt. V. Desistance from offending -- pt. VI. Official interventions.